Development of PjBL-STEM Integrated Student Worksheets (LKPD) in Differentiated Learning to Improve Student’s Scientific Literacy Skills - Rahmah, Karlina; Suyatna, Agus; Distrik, I Wayan; Viyanti, Viyanti; Herlina, Kartini (Sebatik, 2025)
This study aims to develop a Student Worksheet (LKPD) integrated with Project-Based Learning (PjBL) and STEM within differentiated instruction to improve students' scientific literacy skills in a valid, practical, and effective manner. This research is a development study using the ADDIE model, which consists of five stages: Analyze, Define, Design, Implementation, and Evaluation. The results of data analysis show that the developed LKPD is valid for stimulating students' scientific literacy skills on the topic of renewable energy, with an overall validity percentage of 91.93%. This validity includes 92.80% for content, 92.70% for construct, and 90.27% for language aspects. The practicality of the LKPD reached 91.56%, categorized as very practical. The practicality assessment consisted of 90.90% for implementation, 90.62% for readability, and 93.18% for attractiveness. In terms of effectiveness, the LKPD obtained an N-Gain score of 0.5, which falls into the moderate category. The average pretest score was 39.72, which increased to 74.72 on the posttest. Based on the analysis results, it can be concluded that the LKPD integrated with PjBL-STEM and differentiated instruction is valid in terms of content, language, and construct. The practicality of the LKPD is categorized as very practical in terms of implementation, attractiveness, and readability, making it suitable for use in senior high school physics learning (Phase E) under the Merdeka Curriculum with the topic of Renewable Energy. The effectiveness of the LKPD is categorized as moderate, indicating that it can stimulate students’ scientific literacy skills on the topic of renewable energy.